Performance Investigation of 112 Gb/s Hybrid Multiband CAP/QAM Schemes for Short Reach Optical Communication Systems - Majeed, Majidah Hameed; Fyath, Raad Sami (Discoveries in Agriculture and Food Sciences, 2016)
The transmission performance of 112 Gb/s hybrid multiband (HMB) carrier-less amplitude and phase (CAP)/quadrature amplitude modulation (QAM) system over a single mode fiber (SMF) is investigated. Analog squared root-raised cosine (SRRC) orthogonal shaping filters are used to implement the CAP signal that is used to modulate  the 1550 nm (or 1310 nm) continuous wave (CW) laser using Mach-Zehnder modulator. Simulation of HMB CAP-M/QAM-M schemes with M=16, 32, and 64 is performed and the results are compared with that of the corresponding 112 Gb/s single-band of the same scheme. The results show that increasing the roll-off factor r will improve the bit error rate (BER) performance of the system. The optical power required to achieve a BER of for CAP-16/QAM-16 system reduces by 0.75 and 1.88dBm for four-subband and single-band schemes, respectively, when r increases from 0 to 0.4. While the improvement in the laser transmitted optical power for 4-subband and single-band CAP-32/QAM-32 schemes is 0.5 and 0.45dBm, respectively